Metal-Working Fluids Exposure and a Rare Frontoethmoid Lesion - Shahidi, Shayan; Nassimizadeh, Abdul; Sandison, Ann; Ahmed, Shahzada (Case Reports in Otolaryngology, 2020)
This case report describes a unique nasal mass that was difficult to diagnose clinically and histologically. The patient was a middle-aged man employed as a metalworker, and he presented with a unilateral nasal obstruction and a mass arising from the right middle meatus. After a series of investigations, he underwent right-sided sphenoethmoidectomy with excision of a nasal lesion. The surgical specimen presented a major diagnostic challenge for the pathologists and clinicians involved. A series of discussions amongst two different head and neck expert teams combined with detailed clinicopathological correlation resulted in a diagnosis of a granulomatous lesion or pseudotumour related to the ingestion of water-soluble cutting oils, or “Suds oil,” as they are more commonly called. Although occupational exposures to certain inhalants, such as wood dust and formaldehyde, are well-known risk factors for sinonasal lesions, here we present a rare association between a sinonasal lesion and another inhalant, Suds oil, that has not been previously reported in the literature.